2022
DOI: 10.1155/2022/1621210
|View full text |Cite|
|
Sign up to set email alerts
|

A Study on the Effect of Nursing Intervention Based on Health Behavior Change Integration Theory on Patients with Limb Fracture and Its Effect on Limb Function and Self-Efficacy

Abstract: Objective. To assess the impact on nursing care based on the theory of health behavior change integration in patients with limb fracture and its effect on limb function and self-efficacy. Methods. The starting and ending time of this study is from February 2021 to February 2022. In this study, 116 hospitalized patients with limb fracture were selected as the object of study. According to the method of random number table, the patients were divided into study group and control group. The patients of the study c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Under the supervision of medical staff and family members, our patients did Kegel exercises and vaginal weightlifting so as to promote the neurotransmission of motor neurons that project to muscles and improve the contractile force of the pelvic floor muscle fibers. This can effectively promote local pelvic floor blood circulation and muscle metabolism, and improve pelvic floor function and quality-of-life [22,23]. Previous studies have shown that there are many reasons why patients are unable to insist on pelvic floor exercises after surgery [24].…”
Section: Groupmentioning
confidence: 99%
“…Under the supervision of medical staff and family members, our patients did Kegel exercises and vaginal weightlifting so as to promote the neurotransmission of motor neurons that project to muscles and improve the contractile force of the pelvic floor muscle fibers. This can effectively promote local pelvic floor blood circulation and muscle metabolism, and improve pelvic floor function and quality-of-life [22,23]. Previous studies have shown that there are many reasons why patients are unable to insist on pelvic floor exercises after surgery [24].…”
Section: Groupmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%